If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 4y Reorder the terms: 9 + 3x = 4y Solving 9 + 3x = 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = -9 + 4y Combine like terms: 9 + -9 = 0 0 + 3x = -9 + 4y 3x = -9 + 4y Divide each side by '3'. x = -3 + 1.333333333y Simplifying x = -3 + 1.333333333y
| 4x^2-9x=5 | | 2a+5=15 | | 8x-5-2x=2x+1-2x | | 5y^2+19y+12=0 | | 10y^2+38y+24=0 | | 9+3x=-9 | | 2x*4=24x+32 | | 4*2x-8=19-x | | 4(2x)-8=19-x | | 4(4x)-8=19-x | | 3x-6x=18 | | -3x+3=12 | | 7-(3x-2)=12 | | y=(10x+6) | | 10x+5x-35=x+7 | | 3y=2(4y-25) | | -2x+y=4 | | x-15.99=1.55x | | x-1.55x=15.99 | | 4x^3+16x^2+4x+16=0 | | 0.55x+x=15.99 | | 55x+x=15.99 | | 4t-8=-4-7t+3t | | 5(3z-1)-2(z+8)=6(z+1) | | -3a+4+4a=7-25 | | 4x-8y=8 | | -12x+24y=-32 | | y=8 | | -2x+y+3z=20+3x-27+3z+-9 | | 3+5(y+4)=4(y-2)+3 | | 5+2y+5(y-3)=6(y+1) | | 2(3x-4)=7-2x+5x |